Effects of cation stoichiometry on surface morphology and crystallinity of ZnGeN2 films grown on GaN by metalorganic chemical vapor deposition - Md Rezaul Karim; Benthara Hewage Dinushi Jayatunga; Menglin Zhu; Rebecca A. Lalk; Olivia Licata; Baishakhi Mazumder; Jinwoo Hwang; Kathleen Kash; Hongping Zhao (AIP Advances, 2020)
ZnGeN2 films were grown on GaN-on-sapphire templates via metalorganic chemical vapor deposition. Energy dispersive x-ray spectroscopy was used to estimate the Zn/(Zn + Ge) composition ratio in the films. This ratio decreased with an increase in growth temperature but increased with an increase in total reactor pressure or the Zn/Ge precursor flow rate ratio. Systematic mapping of these key growth parameters has allowed us to identify the growth window to achieve ZnGeN2 with stoichiometric cation composition. Compositional and statistical analyses performed on data acquired from atom probe tomography provided insight into the local compositional homogeneity. The cations Zn and Ge did not demonstrate segregation or clustering at the sub-nanometer level. Based on x-ray diffraction 2θ–ω scan profiles and transmission electron microscope nano-diffraction patterns, the films with near-stoichiometric cation ratios were single crystalline with planar surfaces, whereas zinc-rich or zinc-poor films were polycrystalline with nonplanar surfaces. The growth direction of the single crystalline ZnGeN2 films on GaN templates was along the c-axis. Room temperature Raman spectra showed features associated with the phonon density of states, indicating the presence of cation disorder in the lattice. A cathodoluminescence peak associated with transitions involving deep level defects was observed around 640 nm. The intensity of this peak increased by almost 2.5 times as the temperature was reduced to 77 K from room temperature. A similar peak was observed in the photoluminescence spectra collected at 80 K.